Verdens kaldeste sjøvann - Foldvik, Arne; Gade, Herman G (Naturen, 1978)
Publisher: Universitetsforlaget Place: Oslo
Keywords: Sørishavet; Weddellhavet; ekspedisjoner; forskning; observasjoner; oseanografi; sjøvann; vannmasser

Seismikk i Weddellhavet - Haugland, Kristen (Naturen, 1978)
Publisher: Universitetsforlaget Place: Oslo
Keywords: Sørishavet; ekspedisjoner; havbunnen; sedimentologi; seismologi

Om Antarktis, isfjell og havnivå - Maisey, George H (Naturen, 1978)
Publisher: Universitetsforlaget Place: Oslo
Keywords: NARE 1976/77; Sørishavet; ekspedisjoner; geologi; havbunnen; topografi

Biota of the antarctic pack ice: R/V Hero cruise 77-5 - Siniff, D.; Laws, R.; Oritsland, T.; Stirling, I.; Bengtson, J.; Demaster, D.; Reichle, R. (Antarctic Journal of the United States, 1978)
Between 22 October and 20 November 1977, we used National Science Foundation's R/v Hero to conduct studies of Antarctic seals in pack-ice areas of the Antarctic Peninsula. Our principal focus was on crabeater seals, but we also were interested in other pack-ice species, particularly leopard seals. Our work centered on (a) collecting female crabeater and leopard seals for reproductive material depicting various stages of the reproductive cycle, (b) documenting further the social structure and reproductive behavior of crabeater seals, (c) observing daily activity patterns and local movements of crabeater seals at fast-ice concentrations, and (d) investigating crabeater seal behavior at weaning and their interaction with leopard seals.
Keywords: Antarktis; Sørishavet; marin biologi; seler

Hvor driver de antarktiske isfjellene? - Vinje, Torgny E (Naturen, 1978)
Publisher: Universitetsforlaget Place: Oslo
Keywords: Sørishavet; Weddellhavet; drivis; forskning; havis; havstrømmer; isberg; isdrift; issfjell; oseanografi; sjøis; sjøvann

Meteorologiske observasjoner på antarktisekspedisjonen 1978/79 - Vinje, Torgny E. (Været: populærvitenskapelig tidsskrift, 1978)
Keywords: Bouvetøya; Sørishavet; ekspedisjoner; meteorologi